Factores de riesgo higiénicos- sanitarios y su influencia en los servicios de alimentación de la universidad técnica de Babahoyo, durante el primer semestre de 2017. - Arechua Pino, Erika Jessenia (2017)
With the aim of diagnose factors of risk associated to the hygiene-health in food service at the TECHNICAL UNIVERSITY OF BABAHOYO, a descriptive study of field was done in 7 of the 10 establishments. The other 3 are located in the very far extension of Quevedo, so they were excluded. The knowledge of the staff about food service on health and hygiene of National Regulatory Surveillance Agency standards, Control and Health (ARCSA), was assessed. Shortcomings in the 84% of the general conditions, raw materials acquisitions, handling, food preparation, cleaning and disinfection of the staff. Regarding infrastructure of establishments that expend food; a field observation, a survey and a check-list were applied. The 86% of these places lack of a correct infrastructure design to do it. Finally, it is proposed to carry out training regarding hygienic-sanitary regulations, which should be applied by all food handlers.